Perencanaan dan Produksi Gelang Kreatif: Analisis Modal, Bahan, dan Desain - Sri Lismawati S.Dai; Salmatiana Ali; Igrisa, Dila; Hariana (Jurnal Bisnis Digital & Perbankan, 2025)
This study aims to design and produce creative bracelets through capital planning, material selection, and design development. The methods used are literature study and design and planning based on the analysis of capital needs, materials, and product design. The results indicate that with proper capital planning, appropriate material selection, and attractive product design, bracelet production can be carried out efficiently and has the potential to be developed as a micro/small-scale business. This study is expected to serve as an initial reference for bracelet craftsmen in planning production systematically.